Study of Traffic Noise In Brawijaya University Malang - triwinarti, dyah; Wardoyo, Arinto Yudi Ponco (Physics Student Journal, 2014)
This study was aimed to measure the noise loudness generated by the motor vehicle as well as the influence of vehicles on the noise intensity. The sound intensity of the motor vehicle was measured by using a sound level meter. The results of this study show that the intensity of the noise was in the range of 69.48 dB and 71.67dB. Â  KEYWORDS: Noise, Traffic, Motor Vehicle